2020
DOI: 10.21203/rs.3.rs-52430/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Montelukast in Hospitalized Patients Diagnosed with COVID-19

Abstract: Background Several therapeutic agents have been assessed for the treatment of COVID-19, but few approaches have been proven efficacious. Because leukotriene receptor antagonists such as montelukast have been shown to reduce both cytokine release and lung inflammation in preclinical models of viral influenza and acute respiratory distress syndrome, we hypothesized that therapy with montelukast would reduce clinical deterioration as measured by the COVID-19 Ordinal Scale.Methods We performed a retrospective anal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…CysLT1R blockade decreased airway hyper-responsiveness in mice challenged with RSV (94), and attenuated airway hyper-responsiveness, infiltration of inflammatory cells, and excessive mucus production upon reinfection (95). A retrospective analysis in hospitalized COVID-19 patients reported that the risk of clinical deterioration, defined as any increase in the COVID-19 Ordinal Scale value from day1 to day 3 of hospitalization, was significantly lower in patients treated with montelukast, compared with patients not receiving montelukast (96). Several prospective clinical trials are underway to explore the utility of CysLT1R antagonists in treating COVID-19 (Table ).…”
Section: Inhibition Of Pge2 Enhanced Antiviral Immunity and Improved Survival After Iav Infection In Micementioning
confidence: 99%
“…CysLT1R blockade decreased airway hyper-responsiveness in mice challenged with RSV (94), and attenuated airway hyper-responsiveness, infiltration of inflammatory cells, and excessive mucus production upon reinfection (95). A retrospective analysis in hospitalized COVID-19 patients reported that the risk of clinical deterioration, defined as any increase in the COVID-19 Ordinal Scale value from day1 to day 3 of hospitalization, was significantly lower in patients treated with montelukast, compared with patients not receiving montelukast (96). Several prospective clinical trials are underway to explore the utility of CysLT1R antagonists in treating COVID-19 (Table ).…”
Section: Inhibition Of Pge2 Enhanced Antiviral Immunity and Improved Survival After Iav Infection In Micementioning
confidence: 99%
“…In preclinical models of viral influenza and acute respiratory distress syndrome, Montelukast has been shown to decrease both lung inflammation and cytokine release. 47 Montelukast was also shown to reduce eosinophilic inflammation in upper airway inflammatory disease by inhibiting epithelial cell cytokine release and promoting eosinophil survival. 47 Bozek et al found that the rate of Covid-19 infection was significantly lower in a population of elderly patients with severe asthma taking Montelukast, compared to a similar population not taking the drug.…”
Section: What Do We Know About the Treatment Of Asthma During The Covmentioning
confidence: 99%
“…47 Montelukast was also shown to reduce eosinophilic inflammation in upper airway inflammatory disease by inhibiting epithelial cell cytokine release and promoting eosinophil survival. 47 Bozek et al found that the rate of Covid-19 infection was significantly lower in a population of elderly patients with severe asthma taking Montelukast, compared to a similar population not taking the drug. 42 Of the hospitalized patients with Covid-19, those taking Montelukast, did not need respiratory therapy or multidrug antiviral treatment.…”
Section: What Do We Know About the Treatment Of Asthma During The Covmentioning
confidence: 99%
See 1 more Smart Citation
“…Several therapeutic agents have already been assessed for treating COVID-19, but few of them have been shown to be efficacious [ 4 ]. The lack of treatment options is largely due to limited information on other potential treatments and the lack of multicentre clinical trials evaluating their safety and efficacy [ 5 ].…”
mentioning
confidence: 99%